5 Years Experience With Drug Eluting and Bare Metal Stents as Primary Intervention in Transplant Renal Artery Stenosis. Issue 2 (February 2017) - Estrada, Chelsea C.; Musani, Muzammil; Darras, Frank; Suh, Heesuck; Abate, Mersema T.; Mani, Anil; Nord, Edward P.
Abstract : Background: Transplant renal artery stenosis (TRAS) is a common vascular complication after kidney transplantation and is associated with refractory hypertension, volume overload, and graft injury or loss. This article describes 5-year outcomes of endovascular intervention for TRAS with bare metal and drug eluting stents (DES). Methods: We investigated, as a prospective cohort study, patient and graft outcomes after the targeted use of DES for vessel diameter less than 5 mm and bare metal stents (BMS) for vessel diameter greater than 5 mm as the primary management for TRAS. Results: From March 2008 to November 2014, 57 patients were stented for hemodynamically significant TRAS; 29 received DES, 26 received BMS, and 2 patients received both stent types. They were followed up for a mean of 35.1 ± 22.8 months; a subset of these patients who all received DES were followed up for 61.7 ± 17.5 months. Mean serum creatinine declined from 2.87 ± 1.5 mg/dL at the time of intervention to 1.98 ± 0.76 mg/dL ( P < 0.001) at one month follow-up and was 1.96 ±0.92 mg/dL ( P < 0.001) at 35.1 ± 22.8 months. Mean systolic blood pressure declined from 159.05 ± 19.68 mm Hg at time of intervention to 135.65 ± 15.10 mm Hg ( P < 0.001) at most recent visit. Clinically driven restenosis requiring repeat revascularization occurred in 15.7% of patients. Conclusions: Primary stenting with DES and BMS is both successful in the initial treatment of TRAS and also produced an immediate and long-term reduction in serum creatinine and systolic blood pressure.